Global, regional, and national burden of children and adolescents with acute lymphoblastic leukemia from 1990 to 2021: a systematic analysis for the global burden of disease study 2021 - Wang, Lei; Yao, Xue; Yang, Linhua (Frontiers in Public Health, 2025)
BackgroundAcute lymphoblastic leukemia (ALL) is a common cancer in children and adolescents, severely affecting their survival and health. With the discovery of new drugs and improved treatment options, the survival rate of ALL in children and adolescents has improved significantly.MethodsWe used the GBD (global burden of disease) database to collect patients aged 0–19 years (0–5 years, 5–9 years, 10–14 years, 15–19 years) diagnosed with ALL between 1990 and 2021. Disease status and change were analyzed by learning about the prevalence, death, incidence, DALYs (disability-adjusted life years), percentage change, and the estimated annual percentage change (EAPC).ResultsIn 2021, there were 53,485 new cases of childhood and adolescent ALL, 23,991 deaths, and an estimated 1960,922 DALYs. Incidence, deaths and DALYs have declined globally, with only a rise in low-SDI regions. In 2021, middle-SDI regions have the highest cases of prevalence, incidence, deaths, and DALYs, accounting for approximately one-third of the global total. High-SDI regions have the lowest deaths and DALYs. East Asia has the highest prevalence and incidence. Australasia has the lowest death and DALYs. From 1990 to 2021, children and adolescent ALL deaths and DALYs show a declining trend in about 72.5% of countries, with only Sub-Saharan Africa showing an increase. The prevalence of ALL in children and adolescents is higher in males, with the highest cases in patients under 5 years of age.ConclusionOur study highlights the trend of decreasing deaths and DALYs of ALL in children and adolescents. However, there is a need to improve healthcare prevention and timely standardized treatment in developing countries and less developed regions.